Evaluation of the peripheral dose for radiosurgery treatments in simulated targets in different positions of the head of a phantom - Querebalú, Cecilia (2018)
In radiosurgery treatments, there is always an absorbed dose (D) that is deposited outside the treatment field, this D is known as "Peripheral Dose" (PD). The objective of this work was to evaluate PD in 9 anatomical positions (eyes, thyroid, upper lungs, mediastinum, breasts and navel) of an anthropomorphic phantom. The development of the work contemplates the use of the EBT2 radiochromic films, and a photon beam of 6 MV generated in a linear accelerator Clinac 2100C / D. Analyzing the influence of collimator size, greater DP ((150.81 ± 0.97) cGy) was found in the right eye of the phantom for the collimator of 3 cm with a target fixed in the upper right plane of the head of the phantom and its influence with the distance of, a PD of (27.14 ± 1.04) cGy in the thyroid, for a target positioned in the lower left plane of the phantom head for a prescribed dose of 18 Gy. It is concluded that to carry out the optimization during the procedure in radiosurgery it is necessary to know the dependence of the PD with respect to the location of the target, the size of collimator and the distance.